2017
DOI: 10.1096/fj.201700488r
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in postshock mesenteric lymph are key mediators of acute lung injury triggering the macrophage activation via Toll‐like receptor 4

Abstract: Acute lung injury (ALI) is a common cause of morbidity in patients after severe injury due to dysregulated inflammation, which is believed to be driven by gut-derived inflammatory mediators carried mesenteric lymph (ML). We have previously demonstrated that nano-sized extracellular vesicles, called exosomes, secreted into ML after trauma/hemorrhagic shock (T/HS) have the potential to activate immune cells Here, we assess the function of ML exosomes in the development of T/HS-induced ALI and the role of TLR4 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 56 publications
1
68
0
Order By: Relevance
“…In addition to the morphological changes observed herein, polarization of naive macrophages by M1-EVs into M1 macrophages in our study was also indicated by activation of the TLR4-NFκB signaling pathway and an associated increase in iNOS and CD86 expression. Previous research reported that alveolar macrophages were activated (e.g., release of pro-inflammatory cytokines) via the TLR4-NFκB signal pathway when subjected to mesenteric lymph exosomes from hemorrhagic shock rats [26]. In addition, the TLR4-NFκB pathway of human monocytes and monocytederived macrophages was induced when stimulated by EVs derived from calcium ionophore A23187-stimulated monocytes [19].…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the morphological changes observed herein, polarization of naive macrophages by M1-EVs into M1 macrophages in our study was also indicated by activation of the TLR4-NFκB signaling pathway and an associated increase in iNOS and CD86 expression. Previous research reported that alveolar macrophages were activated (e.g., release of pro-inflammatory cytokines) via the TLR4-NFκB signal pathway when subjected to mesenteric lymph exosomes from hemorrhagic shock rats [26]. In addition, the TLR4-NFκB pathway of human monocytes and monocytederived macrophages was induced when stimulated by EVs derived from calcium ionophore A23187-stimulated monocytes [19].…”
Section: Discussionmentioning
confidence: 95%
“…Input from the periphery also modulates the innate pulmonary immune response. In rats, exosomes in mesentery lymph after extra-pulmonary trauma and/or hemorrhagic shock activate alveolar macrophages via TLR4, which mounts a full ALI response 95 . Modulating the mesenteric lymph after traumatic shock in vivo with a pharmacologic vagal agonist results in a reduction in the activity of phosphorylated transcription factor STAT3 in circulating monocytes and attenuates the development of secondary ALI, as well as the systemic inflammatory response 96 .…”
Section: Innate Immune Responses In the Lungs Following Traumamentioning
confidence: 99%
“…Following trauma and hemorrhagic shock, gutderived extracellular vesicles were released into the mesenteric lymphatic system. Intravenous administration of these extracellular vesicles to naïve mice caused lung injury via macrophage TLR4 activation, including increased alveolar vascular permeability and inflammatory cell infiltration [17]. These findings indicate that similar mechanisms may be present in patients who develop ARDS following similar distant (indirect) insults.…”
Section: Contribution Of Extracellular Vesicles To the Pathogenesis Omentioning
confidence: 69%
“…Remarkably, mouse models have indicated that release of extracellular vesicles following distant injury, e.g., traumatic brain injury [16] or trauma and hemorrhagic shock [17], can mediate lung injury. Following trauma and hemorrhagic shock, gutderived extracellular vesicles were released into the mesenteric lymphatic system.…”
Section: Contribution Of Extracellular Vesicles To the Pathogenesis Omentioning
confidence: 99%